Engineering at large scale: Experience from diamond light source - Korsunsky, A; Korsunsky, A (International Association of Engineers, 2010)
Diamond Light Source is the new UK synchrotron facility located at the Harwell Science and Innovation campus near Oxford. It represents the biggest UK investment in science in 30 years, and is set to become the flagship laboratory for multi-disciplinary research. Engineering solutions of remarkable scale and complexity are required for the operation of this facility. On the other hand, engineering science is rapidly becoming an important theme in Diamond's research portfolio. This lecture will cover some aspects of engineering at the Diamond Light Source.